Implementation of marketing mix strategy to increase room occupancy during covid-19 pandemic at the kayon jungle resort - Putri, Ni Made Rian Juniari; Aryana, I Nyoman Rajin; Komala Sari, I Gusti Agung Mas Krisna (Journal of Business on Hospitality and Tourism, 2022)
This research was conducted to know the strengths, weaknesses, opportunities, and threats of The Kayon Jungle Resort during Covid-19 pandemic, business position in IE (Internal – External) matrix, and to find the marketing strategies that can be implemented to increase room occupancy at The Kayon Jungle Resort during Covid-19 Pandemic. Data collection methods that were used in this research were interviews, observation, and questionnaires.  Data analysis techniques were descriptive qualitative analysis, SWOT Analysis, IFAS matrix, EFAS matrix, and IE matrix. The sample in this research used 7 people from Sales and Marketing Department employees, Resort manager, and General Manager of The Kayon Jungle Resort. The results of this research showed 15 internal factors become strengths and 5 internal factors become weaknesses. On the other hand, there were 5 external factors that were opportunities, and 4 external factors become threats. The results of the IE Matrix showed that the position of the company was in the growth strategy (cell II). SWOT analysis produced 9 alternative strategies to increase room occupancy during Covid-19 pandemic at The Kayon Jungle Resort.